AN ANALYSIS ON RECOUNT TEXTS MADE BY THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN 2009/2010 ACADEMIC YEAR - NURIVADATI, LAILY (2010)
This study aims at examining and identifying the elements used in the recount texts made by the first semester students of English Department of Muhammadiyah University of Surakarta in 2009/2010 academic year. This research is descriptive qualitative research. The object of the research is recount texts analysis made by the first semester students of English Department of Muhammadiyah University of Surakarta in 2009/2010 academic year. The data is the elements of recount texts. The method of collecting data is documentation. The technique of data analysis is describing and identifying the percentage of the elements used in recount text. Based on the analysis, the result of the study shows that there are many variations in presenting the elements of recount texts, there are 2 variations in social function, 8 variations in orientation, 5 variations in event, 7 variations in re-orientation, 5 variations in focus on specific participants, one variation in use of material processes, 2 variations in circumstance of place and time, 2 variations in use of past tense, and 5 variations in focus on temporal conjunction. The conclusion that can be drawn from this study is that students’ text has been completed with the elements of recount texts, but many variations are also found there.